Impacts of Mainstream Hydropower Development on Fisheries and Human Nutrition in the Lower Mekong - Golden, Christopher D.; Shapero, Andrew; Vaitla, Bapu; Smith, Matthew R.; Myers, Samuel S.; Stebbins, Elizabeth; Gephart, Jessica A. (Frontiers in Sustainable Food Systems, 2019)
Dams provide energy and irrigation water, but also alter natural water flows that support fisheries. This tradeoff presents a risk for human nutrition in regions dependent on aquatic foods, including the Lower Mekong Basin (LMB), where over 100 dams are planned or in construction. Previous models estimate significant reductions in fishery production resulting from these dams. This study estimates the number of new nutritionally insecure people (i.e., those at risk for nutritional deficiencies) associated with Mekong damming. We calculated population-level nutritional needs based on the Estimated Average Requirements (EARs) for Cambodia and the entire LMB. We then estimated fish-derived nutrient supplies by integrating data on annual fishery production and fish nutrient content for a wide range of species. Finally, we synthesized available literature and modeling results on the impacts of damming on fisheries production, and estimated the consequent impact on inadequate intakes of protein, zinc, niacin, thiamin, riboflavin, and calcium, as well as potential vulnerability to losses of dietary iron. Hydropower development could restrict access to subsistence fish from the Mekong River Basin and lead to increased risk of nutritional deficiencies in Cambodia and the LMB. Our median estimates suggest that by 2030, relative to 2010, inadequate intakes could lead to an increased population at risk of nutritional deficiencies in the LMB by 0.21 to 2.23 million people for protein, 0.12 to 1.17 million people for zinc, 0.41 to 1.58 million people for niacin, 0.47 to 0.87 million people for thiamin, 0.70 to 2.31 million people for riboflavin, and approximately 10,000 people for calcium. This increased population at risk is additional to those currently malnourished. We then calculated that the average iron intake of many age-sex groups (constituting 58% of the population) will be below 150% of their EAR in 2030, indicating a potential risk of increased inadequate iron intake. Fish is the main source of animal source foods and critical micronutrients in the LMB. In the absence of mitigation efforts, any reductions in fishery production could increase already high levels of nutrient deficiency, creating a widespread risk of nutrition insecurity.